2014
DOI: 10.3233/rnn-130351
|View full text |Cite
|
Sign up to set email alerts
|

The “EyeCane”, a new electronic travel aid for the blind: Technology, behavior & swift learning

Abstract: Purpose: Independent mobility is one of the most pressing problems facing people who are blind. We present the EyeCane, a new mobility aid aimed at increasing perception of environment beyond what is provided by the traditional White Cane for tasks such as distance estimation, navigation and obstacle detection. Methods:The "EyeCane" enhances the traditional White Cane by using tactile and auditory output to increase detectable distance and angles. It circumvents the technical pitfalls of other devices, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 38 publications
4
107
1
5
Order By: Relevance
“…This appears to be inconsistent with previous studies showing better performance for blind than for sighted participants when navigating using the TDU SSD [40, 41]. However, a study that tested navigation and obstacle avoidance using the more minimalistic EyeCane SSD, a device designed to have low complexity to make it simple and intuitive to use with minimal training in common with the Miniguide used in the current study, showed similar performance for blind and sighted participants [71]. The difference across studies might reflect the limited amount of training given in our experiment, differences in obstacle size, or differences in the complexity of the devices and tasks used.…”
Section: Discussioncontrasting
confidence: 99%
“…This appears to be inconsistent with previous studies showing better performance for blind than for sighted participants when navigating using the TDU SSD [40, 41]. However, a study that tested navigation and obstacle avoidance using the more minimalistic EyeCane SSD, a device designed to have low complexity to make it simple and intuitive to use with minimal training in common with the Miniguide used in the current study, showed similar performance for blind and sighted participants [71]. The difference across studies might reflect the limited amount of training given in our experiment, differences in obstacle size, or differences in the complexity of the devices and tasks used.…”
Section: Discussioncontrasting
confidence: 99%
“…For this experiment, the EyeCane (Buchs et al, 2014; Maidenbaum, Levy-Tzedek, Chebat, Namer-Furstenberg, & Amedi, 2014; Maidenbaum, Hanassy, et al, 2014), a hand-held device which instantaneously (50 Hz) transforms distance information via sound and vibration such that the closer an object is to the user the stronger the vibration of the haptic actuator and the higher the frequency of the auditory cues. The EyeCane was adapted to include two narrow infra-red (IR) sensors, a sensing range of 1.5 m, such that one of the sensors was directed straight ahead while the other was directed approximately 42 degrees up (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…‘Virtual environments’, which have recently been successfully used for training with sensory substitution devices (Maidenbaum et al 2013, Maidenbaum et al 2014, Chebat et al 2015, Levy-Tzedek et al 2016, Maidenbaum et al 2016), offer an elegant way to solve many of these difficulties. Within the VR context it is easy to generate a varied stimulus set of objects or environments.…”
Section: Perceptual Learningmentioning
confidence: 99%